CENTRO RECREACIONAL - VACACIONAL SUSTENTABLE EN EL CANTÓN EL TRIUNFO - Espinoza Leal, Michelle Arianna (2018)
Esdeconocimientopúblicolosefectosnegativosquelanaturalezahasufridoestosúltimosañosanivelmundial,tomandoencuentaaEcuador,comounpaísmuyricoenbiodiversidadnatural,seconsideranecesariocontribuirconeldiseñodeunproyectoquecontempleunáreanaturalrecreacionalparalaciudaddeGuayaquilqueayudealaconservacióndelmedioambiente.ElCentroRecreacional–VacacionalSustentableubicadoenlaProvinciadelGuayas,CantónElTriunfo,satisfacerálasnecesidadesdelusuariopormediodeespaciosfuncionales,estéticamenteagradablesydemenorimpactoambiental.Ademásdeserunlugaridóneoparapotenciarelturismoecuatoriano,creacióndeplazaslaboralesyunamejorcalidaddevidaalaspersonas.